Alternative hosts and standardization of methods to evaluate the biocontrol activity of mycoinsecticides. (2020)
The entomopathogenic fungi Metarhizium anisopliae (Ascomycota: Clavicipitaceae) and Beauveria bassiana (Ascomycota: Cordycipitaceae) are an alternative for the control of grassland pests (e.g. Rhammatocerus schistocercoides (Orthoptera: Acrididae) and soybean pests (e.g. Cerotoma tingomariana; Coleoptera: Chrysomelidae). To use these microorganisms as active principles of micoinsecticides, it is necessary to have quality control methods (microbiological, physicochemical and biological activity) accuracy, and reproducibility in a given timeframe. For this reason and given the difficulty in obtaining individuals in the field and in the establishment of the rearing of R. schistocercoides and C. tingomariana, we established methods for the routine evaluation of biological activity using alternative hosts. For M. anisopliae directed to the control of R. schistocercoides, the model insects Diatraea saccharalis (Lepidoptera: Crambidae) and Spodoptera frugiperda (Lepidoptera: Noctuidae) were tested, and for B. bassiana directed to the control of the target insect C. tingomariana, the model insects D. saccharalis and Chloridea virescens (Lepidoptera: Noctuidae) were evaluated. D. saccharalis and C. virescens were selected as alternative insects to evaluate the efficacy of M. anisopliae and B. bassiana, respectively. Efficacy was close to 80 % for both pathogens. The methods with the selected alternative insects were standardized and showed that they are repeatable and reproducible under the evaluated conditions